Characterization of potential drug interactions with antimicrobials in a pediatric intensive care unit, Western Amazon - Francimar L. JUCÁ; Andreia F. BRILHANTE; Leonardo K. MELCHIOR; Sammuel C. PINHEIRO; Suyane G. BRAGA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: Characterize the occurrence of potential drug interactions (PDIs) involving antimicrobials in a pediatric intensive care unit (PICU) in Acre state, Western Amazon. Methods: The cross-sectional study analyzed 246 prescriptions from patients up to 11 years old, made in the first 24 hours of hospitalization. Consultations about PDIs were made using Truven Health Analytics Micromedex® Solutions 2.0. classifying according to severity. Results: In the 246 prescriptions analyzed, 28 types of antimicrobials were found, the most prescribed were: ceftriaxone 32.7% (n = 123) and ampicillin 9.3% (n = 35). When analyzing in Micromedex® the information about all the drugs prescribed in this sample, it was obtained in 56% (n = 139) of the prescriptions, 435 PDIs of 64 different types, already described in the literature involving only antimicrobials and antimicrobials with other groups of drugs. Among antimicrobials, ampicillin 28% (n = 26) and gentamicin 23.7% (n = 22) were the most often related to PDIs and in 54.7% (n = 238), the severity of these PDIs it was moderate. Conclusion: We conclude that the PDIs found in the PICU, although well documented, are of serious concern due to their potential effects. The results presented stimulate actions that can guarantee greater safety for hospitalized pediatric patients.